Mucosal immune responses of Atlantic salmon parr following a pathogen breach in a recirculating aquaculture system - Aas, Lena Hovda (UiT The Arctic University of Norway, 2022)
With the increase in the use of recirculating aquaculture system (RAS) in the Norwegian Atlantic salmon (Salmo salar) aquaculture industry, the importance of understanding how pathogen enters and spreads in the system is crucial for its further development. Yersinia ruckeri is a pathogen known for infecting salmonid fish in freshwater stage and it has been shown that the RAS environment favors its proliferation. This study simulated two biosecurity breach scenarios, where pathogen entered the system and triggered a disease outbreak. The first sub-trial simulated a breach where the pathogen entered the RAS facility via the makeup water while the second sub-trial used fish as a vector for the pathogen. Sub-trial one consisted of 3 treatment groups - control, uninfected group, and 2 infected groups, where one group was infected by a single entry (SE) and the other group was infected via a multiple entry (ME). Sub-trial 2 also consisted of three treatment groups - control, uninfected group, and 2 infected groups, where one group was stocked with 10% of the population was infected (i.e., low, 5/50 fish infected) while the other group was stocked with 40% of the population was infected (i.e., high, 20/50 fish infected). For both trials, 3 replicate RAS units were used for each treatment group. Disease development and survival was followed for 14 days, and samples were collected on day 1 and 14 following the biosecurity breach. The innate immune responses were studied in the gills, olfactory organ and distal gut of salmon parr by molecular and histological evaluations. In addition, water quality was monitored during the trial. The results showed that during sub-trial 1, the survival was not dependent whether Y. ruckeri was introduced into the system once or three times. Significant alterations in the expression of immune genes were registered at T14. The genes Lysozyme and Cathelicidin were the genes most heavily affected, and they are both antibacterial defense genes. Sub-trial 2 showed that the mortality among the ...